On the definition and age-dependency of the value of a statistical life: A review and extension - Per-Olov Johansson (Stockholm School of Economics, The Economic Research Institute (EFI), 2002)
The value of preventing a fatality or (saving) a statistical life is an important question in health economics as well as environmental economics. This paper reviews and adds new insights to several of the issues discussed in the literature. For example, how do we define the value of a (statistical) life? Are there really strong theoretical reasons for believing that the value of a life declines with age? The paper derives definitions of the value of a statistical life in both single-period models and life-cycle models. Models with and without actuarially fair annuities are examined, as well as the age-profile of the value of a statistical life.
Keywords: C61; D61; I10; 330; Value of a statistical life; value of preventing a fatality; age-specific values; willingness to pay; Sterblichkeit; Statistische Methode; Theorie